The Resilience of Blind Families in Building a Sakinah Family: Adaptive Strategies and the Role of Islamic Values - Bukido, Rosdalina; L, Sudirman; Sarib, Suprijati; Paikah, Nur; Mokoginta, Anisa Putri Lestari; Makka, Misbahul Munir; Al-Dwairi, Zayed Nawaf Awad (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines how blind couples in Manado, Indonesia, cultivate a sakinah family life that is serene and harmonious despite visual impairment. Using a qualitative case study design, the research engaged four married couples with varying degrees of blindness through semi-structured interviews, non-intrusive observation of daily routines, and brief document reviews. Reflexive thematic analysis identified three interlocking processes of family resilience that anchor these households: (1) meaning making, in which Islamic virtues such as ṣabr (patience), shukr (gratitude), and tawakkul (trust in God) regulate emotion, guide decisions, and sustain hope; (2) communication, marked by de escalation strategies, turn-taking when one spouse is upset, and the creative use of auditory and tactile cues for coordination; and (3) organization, featuring adaptive role-sharing based on actual capacity and health rather than rigid gender prescriptions. Surrounding these processes is a multilayered social infrastructure of support that ranges from kin and neighbors to mosque communities and disability organizations, supplemented by voice-based technologies and informal income strategies. This article presents an operational mapping of sakinah indicators to observable family outcomes, clarifies how paid versus unpaid proximal assistance functions in practice, and shows how faith-informed coping integrates with disability-inclusive support. Policy implications include designing family programs that are both disability-aware and religion sensitive, strengthening local networks that enable independent living, and recognizing flexible caregiving arrangements within households headed by persons with disabilities.